2017
DOI: 10.21873/anticanres.12055
|View full text |Cite
|
Sign up to set email alerts
|

(–)-Epigallocatechin-3-gallate Down-regulates Doxorubicin-induced Overexpression of P-glycoprotein Τhrough the Coordinate Inhibition of PI3K/Akt and MEK/ERK Signaling Pathways

Abstract: Abstract. Background/Aim: (-)-Epigallocatechin-3-gallate (EGCG) has been indicated to regulate the function of Pglycoprotein (P-gp), which is a drug transporter encoded by the MDR1 (ABCB1) gene. P-gp expression is induced by doxorubicin (DOX). We aimed to clarify the mechanisms and inhibitory effects of EGCG on DOX-induced P-gp expression in HepG2 cells. Materials and Methods: Rhodamine 123 (Rho123) was used for P-gp substrate. Western blotting and polymerase chain reactions (PCRs) were conducted using specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 26 publications
0
18
0
Order By: Relevance
“…Mechanistically, EGCG pre-treatment significantly attenuated the corticosterone-mediated inhibition of ERK1/2 and PI3K/AKT phosphorylation, which are critical merging points for many signaling cascades involved in the regulation of cell survival, cell growth and proliferation under physiological and pathophysiologic conditions [ 41 , 42 ]. EGCG has been shown to modulate ERK and PI3K/AKT signaling systems in different tissues and cell lines [ 1 , 4 , 43 45 ]. In the nervous system, a low level of ERK activation is needed to promote neuronal growth, thereby facilitating neuronal plasticity and survival [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mechanistically, EGCG pre-treatment significantly attenuated the corticosterone-mediated inhibition of ERK1/2 and PI3K/AKT phosphorylation, which are critical merging points for many signaling cascades involved in the regulation of cell survival, cell growth and proliferation under physiological and pathophysiologic conditions [ 41 , 42 ]. EGCG has been shown to modulate ERK and PI3K/AKT signaling systems in different tissues and cell lines [ 1 , 4 , 43 45 ]. In the nervous system, a low level of ERK activation is needed to promote neuronal growth, thereby facilitating neuronal plasticity and survival [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, EGCG enhanced the inhibitory effects of sorafenib on anaerobic HCC-cell growth and in an HCC-xenograft mouse model. Recently, it has been shown that EGCG attenuates the overexpression of Pgp induced by Dox in HepG2 cells by inhibiting the ERK–MAPK and PI3K–Akt signaling pathways 62. Finally, a new molecular mechanism underlying the EGCG-mediated autophagic modulation of AFP in HepG2 cells has been proposed by Zhao et al63 Taken together, all these findings suggest that EGCG could be conceivably utilized for counteracting and treating HCC by acting on different molecular mechanisms.…”
Section: Preclinical Assessments Of Egcg Anticancer Effects In Hepatomentioning
confidence: 95%
“…In the CAMARADES analysis (Table 3), we found that all the studies considered were published in peer-reviewed journals and showed detailed biochemical/tissue evaluations and professional statistical analysis. The newest studies8,62 obtained the highest score (9/11) despite the lack of any allocation-concealment technique, mandatory to prevent selection bias. This criterion is often underestimated, as demonstrated in our previous CAMARADES evaluations 64.…”
Section: In Vivo Investigations: Animal Models and Egcg Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Particularly, cross talk between these two pathways has been well illustrated in previous studies. 15 17 Moreover, several studies have shown that inhibition of the ERK pathway enhanced the antitumor activity of RAD001 in pediatric gliomas, 18 neuroblastoma, 19 and acute myelogenous leukemia. 20 Thus, the aim of this study was to identify the underlying mechanisms and biochemical pathways involved in RAD001 resistance in RCC.…”
Section: Introductionmentioning
confidence: 99%